Echocardiography in children with Down syndrome - Al-Biltagi, Mohammed A (Baishideng Publishing Group Co., Limited, 2013)
Congenital heart disease is a common problem in children with Down syndrome (DS). Echocardiography plays an important role in the detection of both structural and functional abnormalities in this group of patients. Fetal echocardiography can help in the early recognition of DS by detecting soft markers of DS, but its main role is to define the exact nature of the suspected cardiac problem in the fetus. Postnatal echocardiography is mandatory in the first month of life for all neonates with DS. It is also indicated before any cardiac surgery and for serial follow-up after cardiac surgery. In this article, we discuss the types and mechanism of cardiac abnormalities in DS children and the role of both fetal and postnatal echocardiography in the detection of these abnormalities.